ESTIMATION OF LAND SURFACE TEMPERATURE-ASSESSMENT WITH REMOTE SENSING DATA FOR URBAN HEAT ISLAND IN BATAM MUNICIPALITY - Wenang Anurogo; Rapena Tandon Cahayanti Sidabutar; Muhammad Zainuddin Lubis; Hidayat Panuntun; Cahyo Budi Nugroho; Muhammad Sufwandika (GeoEco, 2023)
Urban Heat Island (UHI) is a phenomenon where the surface temperature in urban areas is higher than in the surrounding area or in open-air areas. Hilly city continues to increase every year. Because of that, it needed an effort at the city-level urban heat island on Batam Island. Through the Thermal Landsat 8 channel image recording May 24, 2018 sensing data can be used to complete the heat calculation of the urban heat Island on Batam Island. This research aims to determine the variation of Urban Heat Island (UHI) effect on land cover in the research area. This research uses LST and maximum likelihood multispectral classification for the land cover area and NDVI transformation. The results of the processing are obtained with an R2 value of 0.872324 with a UHI intensity of 0-8.06 ̊ C. This shows the amount needed by Urban Heat Cities in Batam Island specifically in urban areas such as Batu Ampar District, Batam Kota, Bengkong, Batu Aji, Lubuk Baja, Sagulung, and Sekupang